The Ethyl Acetate Extract of Mangosteen Peel Cream Attenuates Ultraviolet B Radiation-Induced Apoptotic Cell Death Via Antioxidant Effect By Regulation TNF-Α and Caspase 3 in Guinea Pig Skin (Bangladesh Journal of Medical Science, 2022)
Background:UV radiation induced ROS cause DNA damage mainly due to photoaging. Lipid peroxidation due to UV exposure also produces non-toxic metabolite compounds namely malonyldialdehyde (MDA). Upregulation of TNF-α is key to the initial response to ultraviolet B (UVB) exposure by keratinocytes. The basal cell layer is the most affected undergoes to apoptosis and can be detected through caspase 3 which is the main executor of apoptosis. Mangosteen peel (Garcinia mangostana Linn.)contains xanthon known as alpha mangosteen, the most attention today is as an antioxidant. The purpose of this study is to determine the antioxidant effects of ethyl acetate extract in mangosteen peel cream on MDA levels, anti-inflammatory effects on TNF-α levels and anti-apoptosis effects on caspase 3 levels, testedin guinea pig skin exposed to UVB rays.Methods :This study uses a post test only control group design using female guinea pig (Cavia porcellus) who obtained, cared, and treated at the Wates Veterinary Center, Yogyakarta. Consisting of 20 animals divided randomly into 4 treatment groups.P1: normal group, without any treatment. P2: exposed to UVB light. P3: exposed to UVB light and given base cream. P4: exposed to UVB light and given 12% extract mangosteen peel cream. MDA were analyzed by the TBARS method (nmol/ml). Levels of TNF-α epidermis were obtained by the TNF alpha Elisa antibodies Kit (pg/ml). Levels of caspase 3 epidermis were obtained by the caspase antibody 3 Elisa Kit (pmol / L).Results:Post Hoc statistical analysis showed that MDA serum levels of P4 group was significantly lower compared to P2 group(p